Explosive Activity on Kīlauea's Lower East Rift Zone Fueled by a Volatile‐Rich, Dacitic Melt. (11th February 2022) - Wieser, Penny E.; Edmonds, Marie; Gansecki, Cheryl; Maclennan, John; Jenner, Frances E.; Kunz, Barbara; Antoshechkina, Paula; Trusdell, Frank; Lee, R. L.; EIMF,
Abstract: Magmas with matrix glass compositions ranging from basalt to dacite erupted from a series of 24 fissures in the first 2 weeks of the 2018 Lower East Rift Zone (LERZ) eruption of Kīlauea Volcano. Eruption styles ranged from low spattering and fountaining to strombolian activity. Major element trajectories in matrix glasses and melt inclusions hosted by olivine, pyroxene and plagioclase are consistent with variable amounts of fractional crystallization, with incompatible elements (e.g., Cl, F, and H2 O) becoming enriched by 4–5 times as melt MgO contents evolve from 6 to 0.5 wt%. The high viscosity and high H2 O contents (∼2 wt%) of the dacitic melts erupting at Fissure 17 account for the explosive Strombolian behavior exhibited by this fissure, in contrast to the low fountaining and spattering observed at fissures erupting basaltic to basaltic‐andesite melts. Saturation pressures calculated from melt inclusion CO2 ‐H2 O contents indicate that the magma reservoir(s) supplying these fissures was located at ∼2–3 km depth, which is in agreement with the depth of a dacitic magma body intercepted during drilling in 2005 (∼2.5 km) and a seismically imaged low Vp / Vs anomaly (∼2 km depth). Nb/Y ratios in erupted products are similar to lavas erupted between 1955 and 1960, indicating that melts were stored and underwent variable amounts of crystallization in the LERZ for >60 years before being remobilized by a dike intrusion in 2018. We demonstrate that extensive fractional crystallization generates viscous and volatile‐rich magma with potential for hazardous explosive eruptions, which may be lurking undetected at many ocean island volcanoes. Plain Language Summary: During the first 2 weeks of the 2018 eruption of Kīlauea Volcano, Hawai'i, a wide variety of magma compositions were erupted from 24 separate fissures. Of particular interest is the magma erupted at Fissure 17, which was much more explosive than nearby fissures, throwing large pieces of molten rock several 100 m into the air, causing a serious injury. The explosivity of volcanic eruptions is partially controlled by the viscosity of the magma (how easily it can flow), and partially by the amount of dissolved H2 O and CO2 (which exsolve like bubbles in a carbonated beverage as the melt ascends to the surface). We show that melts erupted at Fissure 17 were significantly more viscous and H2 O‐rich than the melts erupted more passively at nearby fissures. These two factors account for the explosive eruptive style of this fissure. Using the relationship between the amount of dissolved H2 O and CO2 and pressure, we show that erupted magmas were stored at ∼2 km depth below the surface since at least 1955–1960 CE. Key Points: The first 2 weeks of the 2018 Kīlauea eruption tapped melts undergoing variable amounts of fractionation at ∼2–3 km depth over >60 years Saturation pressures calculated from melt inclusion volatile contents align with drilling encounters and seismic anomalies The strombolian explosions at Fissure 17 result from the high viscosity and the high H2 O contents of these dacitic melts